(untitled) (Journal of Applied Learning and Teaching, 2023)
Critical teacher education emerged as a response to the liberal, hegemonic, and power-oriented world that affected teacher education as well. Albeit widely discussed, moving towards becoming this type of teacher educator is neither easy nor fast. This autoethnographic narrative study describes my journey as a teacher educator from a non-critical, product-oriented, passive teacher educator to a more critical, process-oriented, active teacher educator who learns, questions, relearns, and unlearns. The data are gathered from different sources of my personal portfolio, including training diaries, field notes, memories, feedback, and observation. The findings of the study reveal the underlying factors that shape our thoughts, beliefs, and practices and how we can gain voice and agency and transform into critical teacher educators.